Analysis of β-lactam, azithromycin and fosfomycin resistance in non-typhoidal Salmonella: Characterisation of an S. Infantis plasmid. Issue 7 (10th July 2020) - Lee, Winnie; Bloomfield, Samuel; Mather, Alison; Edwards, Andrew; Chattaway, Marie; Nair, Satheesh
Abstract : Non-typhoidal Salmonella (NTS)infections are associated with high morbidity and mortality. β-lactams are used as first-line treatment but resistance to these has increased considerably in recent years. Azithromycin and fosfomycin are used as alternatives; however, the incidence of resistance in these drugs is also increasing. Epidemiological surveillance on 35, 372 NTS received by Public Health England was conducted for analysis of demographics, including global travel. Genomic typing and antimicrobial resistance data for Salmonellaisolates were used to determine the prevalence of β-lactam, azithromycin and fosfomycin resistance in NTSover a four year period. No isolates were resistant to β-lactams, azithromycin or fosfomycin alone but all isolates were resistant to multiple antimicrobial classes. IncHI2, IncY and IncN plasmids were predominantly found in the most multi-drug resistant isolates. Multi-drug resistance (MDR) was particularly a concern in the S. Infantis population. Therefore, long read sequencing was used to characterise an MDR S. Infantis isolate. Three drug regions were identified in a IncFIB, a mega plasmid identified in this isolate. The resistance determinants fosA, arsA, arsD and blaCTXM65, were discovered on the same drug region. Analysis of IncFIB in this S.Infantis isolate revealed 99% similarity to a IncFIB plasmid in S. Infantis isolated from chickens in the USA. Thishas not been reported before, warranting efforts for enhanced surveillance programmes to identify sources of emerging resistance, which will aid in establishing control measures for prevention of spread of resistance.